Urdu translation and validation of clinically useful anxiety outcome scale in Pakistan: ‘an observational study’ - Yasmeen Wajid; Humaira Jami; Aisha Zubair; Arooj Mujeeb (Journal of the Pakistan Medical Association, 2022)
Objective: To translate and evaluate the psychometric properties of the Clinically Useful Anxiety Outcome Scale on Urdu-speaking population. Method: The observational validation study was conducted in Rawalpindi and Islamabad, Pakistan, from January 2018 to December 2019 in two phases. In the first phase, the Clinically Useful Anxiety Outcome Scale was forward and backward translated, while in the second phase, the translated scale was validated on a human sample comprising subjects in clinical and nonclinical settings. Item-to-total correlation, internal consistency and test-retest reliabilities were checked with inter-group comparisons. To find out the level of language equivalence between the original and the translated versions, a separate sample of bilingual participants was raised. Data was analysed using SPSS 22. Continue